Healing While Hurting: The Unspoken Burden of Female Medical Residents in Pakistan - Iqbal Haider (International Journal of Pathology, 2024)
Gender stress, particularly among female healthcare professionals undergoing postgraduate training, is a pressing issue that warrants urgent attention in Pakistan’s medical landscape. This pressure is particularly intense in areas like gynecology, pediatrics, cardiology, gastroenterology, and general medicine, where there’s a high demand for female providers. The convergence of family stressors, marital status, parental responsibilities, financial constraints, grueling work hours, and a shortage of female healthcare workers exacerbates the problem, posing significant challenges to both individuals and the healthcare system at large.